Supply Market Intelligence, Supply Management Influence, Supplier Integration and Sourcing Enterprise Performance as Antecedents of Buyer Financial Performance - Jatturong Ploenhad; Ampika Laoprawatchai; Pornpanna Laoprawatchai; Ratchaneewan Sujarit (International Journal of Supply Chain Management, 2020)
The prime objective of the present study is to examine the impact of supply market intelligence and supply management influence on the financial performance of the buyer. Moreover, the impact of supplier integration and sourcing enterprise performance on buyer financial performance is examined as well. The questionnaires were distributed among 476 customers of automotive sector of Indonesia and 400 questionnaires were received back. The response rate was 84%. Moreover, in this study, Partial Least Square (PLS) path modeling was employed as a methodological technique to test and examine the hypotheses set and the effects within the constructs. All the proposed hypothesis was accepted. The findings of the study are important for the policy makers of the automotive sector of Indonesia.